THE EFFECT OF COTTON YIELD WHEN PLANTED AS A COMPATIBLE AND RECIPROCATING CROPS WITH CANNON AND SOY CROPS (International journal of artificial intelligence, 2024)
In this article, information on the growth, development and impact of cotton crops as a repeated crop in the light gray soils of the Syrdarya region, which are being grazed, has been developed.